GERAKAN REMAJA MINUM TABLET TAMBAH DARAH UNTUK MENCEGAH ANEMIA (GEMA GEMIA) DENGAN METODE KAP DI SMPS MITRA JEMBER - Luthviatin, Novia; Erik Gunawan; Fenny Gita Lestari Putri; Syintia Dwi Pramesti; Anggita Rizky Suci Irawan; Wahyu Dwi Lukita; Adinda Tira Octavia (P3M Universitas Aisyiyah Surakarta, 2025)
Anemia in adolescents is a global health problem, especially in developing countries. Teenage girls are more susceptible to anemia because they experience menstruation every month, which causes them to lose significant amounts of blood. Anemia can affect student learning achievement. The outreach activity of the Youth Movement to Routinely Take Blood Supplement Tablets (TTD) to Prevent Anemia (Gema Gemia) to 35 female students of SMPS Mitra Jember was carried out using the health education method through interpersonal communication (KAP). The media used are flipcharts and educational videos. Data was collected through pre and post-test questionnaires, which were then analyzed using the paired sample t-test. The analysis results showed that there was an average difference between the pre-test and post-test scores (p=0.000), which means that there was an influence of providing health education on knowledge about anemia and TTD among young women at SMPS Mitra Jember. Furthermore, similar education needs to be carried out in other schools because many young women still do not know the importance of TTD in preventing anemia. Keywords: Anemia; blood supplement tablets; educational videos; flipcharts; interpersonal communication (KAP); junior high school; teenage girls